2014
DOI: 10.1037/a0031766
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment before and after combat-related deployment among active-duty United States Air Force maltreating parents.

Abstract: Objective: To conduct the first population-based study comparing the frequency of child maltreatment among active-duty United States Air Force (USAF) maltreating parents before and after combat-related deployment. Method: By combining archival databases, we identified 2,287 children with a total of 2,563 substantiated maltreatment incidents perpetrated by USAF parents who deployed during an 85-month study period during Operation Iraqi Freedom/Operation Enduring Freedom. Results: Contrary to expectations, overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 42 publications
3
18
3
Order By: Relevance
“…We also found that maltreatment rates were consistently lower following deployment when child maltreatment was mild (e.g., did not involve offender alcohol use, did not result in injury to the child victim, and was rated as mild in severity) or when the incident involved emotional abuse. These findings are consistent with results reported in prior research of maltreating parents in deploying families (e.g., Thomsen et al, 2014) and with prior research examining the relationship between combat-related deployments and spouse abuse (i.e., Rabenhorst et al, 2013), which found postdeployment increases in incidents involving severe abuse and offender alcohol use.…”
Section: Child Maltreatment Rates Predeployment and Postdeployment Ansupporting
confidence: 91%
See 3 more Smart Citations
“…We also found that maltreatment rates were consistently lower following deployment when child maltreatment was mild (e.g., did not involve offender alcohol use, did not result in injury to the child victim, and was rated as mild in severity) or when the incident involved emotional abuse. These findings are consistent with results reported in prior research of maltreating parents in deploying families (e.g., Thomsen et al, 2014) and with prior research examining the relationship between combat-related deployments and spouse abuse (i.e., Rabenhorst et al, 2013), which found postdeployment increases in incidents involving severe abuse and offender alcohol use.…”
Section: Child Maltreatment Rates Predeployment and Postdeployment Ansupporting
confidence: 91%
“…Using an Army sample, McCarroll et al (2008) found that child neglect rates increased following combat deployment. However, using an USAF sample, we (Thomsen et al, 2014) found that child neglect was lower postdeployment compared to predeployment. Thus, we hypothesized that child neglect rates would be lower postdeployment compared to predeployment in our USAF sample.…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…Existing studies of young children in military families have found elevated levels of internalizing and externalizing behavior problems both during and following deployment (Chartrand et al, ; U.S. Department of Defense, ). Direct effects of deployment, although stronger when separations are lengthy, may be more modest overall than indirect effects that are mediated through parents' characteristics and behavior; the predeployment period is not exempt (Jordan et al, ; IOM, ; McCarthy et al, ; Thomsen et al, ).…”
Section: The Context Of Child–mother Attachment Relationships In Milimentioning
confidence: 99%